Managerial and Customer Costs of Price Adjustment: Direct Evidence from Industrial Markets - Zbaracki, Mark J.; Ritson, Mark; Levy, Daniel; Dutta, Shantanu; Bergen, Mark (The Review of Economics and Statistics, 2004)
International audience